Digital Comic Learning Media Based on Entrepreneurship to Instill an Entrepreneurial Spirit in Elementary School Students - Arini, Ni Kadek Merna; Tegeh, I Made; Jayanta, I Nyoman Laba (Universitas Pendidikan Ganesha, 2024)
This research is morivated by students' low entrepreneurial spirit and the suboptimal use of learning media in educational activities. This study aims to develop a design for entrepreneurship-based digital comic learning media, analysis of media content validity, analysis of media practicality, and analysis of media effectiveness on the entrepreneurial spirit of elementary school students. This study uses a 4D model focusing on entrepreneurship-based digital comic learning media, examining content validity, material, user responses, and media effectiveness. Data collection was carried out using a questionnaire method. This study uses four methods for data analysis: the Gregory formula for media and material expert validity and practicality, the CVR/CVI formula for effectiveness, the Aiken formula for media content validity, the mean formula for student responses, and the correlated t-test for product effectiveness. The study results show that the digital comic media has high content validity, the interactive materials also score high in validity, the media is highly practical, and it significantly fosters the entrepreneurial spirit of elementary school students. It can be concluded that, innovation of digital comic media based on entrepreneurship, has proven effective in instilling the entrepreneurial spirit of fifth grade elementary school students.